Bridging knowledge gaps: An observational study on HPV awareness and misconceptions among young adults in China - Minrui Li; Lili Liang; Xuanyan Chen; Zhoujun Zhu; Chenyan Fang; Runan Zhou (PLoS ONE, 2025)
Human Papillomavirus (HPV) is a sexually transmitted infection associated with genital warts and multiple cancers. HPV awareness and vaccine coverage remain low in mainland China. With the rise of digital social media, young people increasingly acquire knowledge and information online, influencing their perceptions and decisions. Impact of social media on HPV knowledge and vaccine hesitancy remains unclear. The study aimed to assess the knowledge and awareness of HPV and its vaccines hesitancy among young adults in China using an online structured questionnaire with implied consent. Our findings showed that 94.4% of respondents had heard of HPV, with most aware of its sexual transmission and risks to both men and women. However, gaps in knowledge and misconceptions were identified, particularly concerning the asymptomatic nature of HPV infections and the lack of effective antiviral treatments for HPV. Misconceptions about HPV and vaccine safety were notable, contributing to vaccine hesitancy. Yet 78.4% of participants believed in the effectiveness of HPV vaccine, and 83.5% expressed their willingness to receive vaccination if recommended by a doctor. Although overall awareness of HPV and HPV vaccination was high, significant knowledge gaps and misconceptions remain. Thereby reshaping public perception and enhancing awareness, trust and motivation for HPV vaccination are under challenge. Addressing misinformation through strategic educational initiatives could enhance trust in HPV vaccination and improve coverage, ultimately reducing the burden of HPV-related diseases in China.